The Role of Celebrity Endorsers and Brand Awareness on Purchasing Decision through Trust in E-Commerce Consumers in Yogyakarta - Barus, Hendra Budianto; Fadhilah, Muinah; Cahyani, Putri Dwi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to determine the effect of celebrity endorsers and brand awareness on purchasing decisions through trust in Tokopedia E-Commerce consumers in Yogyakarta. This research uses quantitative methods. The population is Tokopedia E-Commerec consumers in Yogyakarta. The sampling technique used is nonprobability sampling by distributing questionnaires to 100 respondents measured on a Likert scale. For data analysis techniques using multiple linear regression analysis methods. The results of this study indicate that celebrity endorsers (X1) have a positive and significant effect on purchasing decisions (Y) and trust (Z), brand awareness (X2) has a positive and significant effect on purchasing decisions (Y) and trust (Z), trust (Z) has a positive and significant effect on purchasing decisions (Y). And there is a positive and significant influence of celebrity endorsers and brand awareness on purchasing decisions through trust.